Clinical Outcomes of Descemet Membrane Endothelial Keratoplasty in Saudi Patients - Showail M; AlJehani R; Almarzouki N; Jamjoom HG; Tash R; Abusharkh FH (Clinical Ophthalmology, 2025)
Mahmood Showail,1,2 Reham AlJehani,1,2 Nawaf Almarzouki,1,2 Hanan G Jamjoom,1,2 Rawan Tash,2 Fatmah H Abusharkh2 1Department of Ophthalmology, King Abdulaziz University Hospital, Jeddah, Saudi Arabia; 2Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Mahmood Showail, Department of Ophthalmology, King Abdulaziz University Hospital, P.O. Box 80215, Prince Majid Road, Al Sulaymaniyah, Jeddah, 21589, Saudi Arabia, Tel +966504365380, Email mshowail@gmail.comPurpose: Descemet membrane endothelial keratoplasty (DMEK) is a well-known surgical procedure for managing corneal endothelial diseases. However, the applicability of DMEK across different populations remains unclear. This study aimed to evaluate the outcomes of DMEK in patients from Saudi Arabia and compare them with international standards.Patients and Methods: This retrospective record review evaluated the medical records of 12 patients who underwent DMEK at King Abdulaziz University Hospital from October 2022 to December 2023. Postoperative outcomes, including best-corrected visual acuity, intraocular pressure (IOP), graft attachment, and rates of rejection and re-bubbling, were evaluated at the 1-month follow-up visit.Results: Of the 12 patients, 10 were included in the final analysis (mean age, 65.5 ± 8.69 years; men, n = 3, 30%; women, n = 7, 70%). The most common indications for DMEK were pseudophakic bullous keratopathy (50%) and Fuchs’ endothelial corneal dystrophy (40%). Postoperatively, the median best-corrected visual acuity improved significantly from 0.5 (range, 0.5– 1) to 0.1 (range, 0.1– 0.3) (P = 0.039). The median IOP remained stable, with no significant change observed postoperatively. None of the patients experienced graft rejection or failure; however, 20% required re-bubbling. The mean central corneal thickness significantly decreased from 676 ± 103.71 μm preoperatively to 506.2 ± 27.57 μm postoperatively (P < 0.001).Conclusion: This study demonstrated that DMEK provides effective visual improvement with low complication rates in patients from Saudi Arabia, comparable to the findings obtained in international studies. These findings may encourage wider adoption of DMEK among corneal surgeons in Saudi Arabia.Keywords: graft attachment, Saudi Arabia, DMEK